2010
DOI: 10.1007/s10552-010-9582-x
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of filtered and boiled coffee and the risk of incident cancer: a prospective cohort study

Abstract: These findings demonstrate, for the first time, the potential relevance of brewing method in investigations of coffee consumption and cancer risk, but they must be confirmed in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 34 publications
(49 reference statements)
0
116
2
Order By: Relevance
“…If coffee consumption was indicated by ml (or g), 21,22 we defined 250 ml (or 250 g) of coffee equal to 1 cup. If coffee consumption was measured in a times/day (or occasions/day or drinks/day) scale, 11,23,24 we assumed the scale equals to cups/day.…”
Section: Methodsmentioning
confidence: 99%
“…If coffee consumption was indicated by ml (or g), 21,22 we defined 250 ml (or 250 g) of coffee equal to 1 cup. If coffee consumption was measured in a times/day (or occasions/day or drinks/day) scale, 11,23,24 we assumed the scale equals to cups/day.…”
Section: Methodsmentioning
confidence: 99%
“…As the characteristics presented in Table 1, there were 8 studies [9,[13][14][15][23][24][25][26], including 312,993 volunteers in this meta-analysis. And after 10-18 years follow-up, a total of 1429 volunteers were diagnosed with gastric cancer.…”
Section: Characteristics and Quality Assessment Of The Eligible Studiesmentioning
confidence: 99%
“…In addition, previous studies have found that smoking, alcohol intake, salt or salted food intake, and low intake of fruit and vegetables were the known risk factors for development of stomach cancers [4][5][6]. Coffee is one of the most widely consumed beverages in the world, especially in Sweden and the United States [7][8][9]. It is well known that coffee contains numerous substances with potentially genotoxic and mutagenic properties [10][11][12], which has raised the concern that high consumption of coffee might increase the risk of many chronic diseases and the development of various malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1980s, coffee (a major source of caffeine) was related to pancreatic cancer risk in a hospital-based case-control study, where the comparison group included patients with chronic diseases, including other cancers [12]. Subsequent studies did not consistently confirm the relation [13], thus the issue remains open to discussion [14].…”
Section: Introductionmentioning
confidence: 99%